Penyakit Hirschsprung di Indonesia: Faktor Potensial yang Berkontribusi dan Analisis Silsilah - Yuni Ahda; Khairunnisa; Zuhrah Taufiqa; Diana Lyrawati; Risa Ukhti Muslima (Jurnal Penelitian Pendidikan IPA, 2025)
Hirschsprung’s disease (HD) has a complex origin involving genetic factors. While HD cases have been documented in Indonesia, the genetic inheritance is unexplored. This study aims to update HD in Indonesia, determine the inheritance pattern through pedigree analysis, and identify the non-genetic factors contributing to HD, including parental demographics and maternal aspects. A cross-sectional survey was conducted with 87 respondents across Indonesia. The results revealed a male-to-female incidence ratio of 1.90:1, with the ultra-short segment being the most common type (75.86%), and familial cases accounted for 8%. Seventeen patients exhibited other congenital abnormalities, with pneumonia, redundant colon, and cardiac defect as the highest cases. Over 70% of the parents were aged 20-35 and had relatively high education and income levels. Notably, nearly half of the mothers experienced food aversion in the first trimester (n=38) and frequently consumed fast or instant food during pregnancy (n=33). The study confirmed that HD follows an autosomal recessive inheritance pattern. These findings emphasize the role of genetic inheritance in incidents of HD, which is valuable for developing early detection strategies and providing genetic counseling for at-risk families. Maternal lifestyle factors may play a role in the development of HD, which needs further investigation.